Modelled black carbon radiative forcing and atmospheric lifetime in AeroCom Phase II constrained by aircraft observations - Samset, B. H.; Myhre, G.; Herber, A.; Y. Kondo; Li, S. -M.; Moteki, N.; Koike, M.; Oshima, N.; Schwarz, J. P.; Balkanski, Y.; Bauer, S. E.; Bellouin, N.; et al. (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2014)
Atmospheric black carbon (BC) absorbs solar radiation, and exacerbates global warming through exerting positive radiative forcing (RF). However, the contribution of BC to ongoing changes in global climate is under debate. Anthropogenic BC emissions, and the resulting distribution of BC concentration, are highly uncertain. In particular, long-range transport and processes affecting BC atmospheric lifetime are poorly understood. Here we discuss whether recent assessments may have overestimated present-day BC radiative forcing in remote regions. We compare vertical profiles of BC concentration from four recent aircraft measurement campaigns to simulations by 13 aerosol models participating in the AeroCom Phase II intercomparison. An atmospheric lifetime of BC of less than 5 days is shown to be essential for reproducing observations in remote ocean regions, in line with other recent studies. Adjusting model results to measurements in remote regions, and at high altitudes, leads to a 25% reduction in AeroCom Phase II median direct BC forcing, from fossil fuel and biofuel burning, over the industrial era. The sensitivity of modelled forcing to BC vertical profile and lifetime highlights an urgent need for further flight campaigns, close to sources and in remote regions, to provide improved quantification of BC effects for use in climate policy.